20. ASSESSMENT OF THE EFFICACY OF COMBINED POPLITEAL AND ADDUCTOR CANAL NERVE BLOCKS IN POSTOPERATIVE PAIN MANAGEMENT FOLLOWING BELOW-KNEE SURGERY (Vietnam Journal of Community Medicine, 2024)
Background: Postoperative pain following below-knee surgeries is often of moderate to severe intensity, requiring effective pain management strategies. Various methods are employed for pain management in these cases, each offering unique benefits and drawbacks. Recent evidence suggests that combining popliteal nerve block with adductor canal block can provide better pain control, minimize postoperative Opioid requirements, enhance patient satisfaction, and improve the overall quality of postoperative care. The aim of this study is to evaluate the efficacy of this combined anesthetic approach with regard to postoperative pain management, reduction in Morphine consumption, and improving patient satisfaction.Methods: This study included 44 patients undergoing below-knee surgery at Hue University of Medicine and Pharmacy Hospital from August 2023 to August 2024. Participants received a popliteal nerve block in conjunction with a saphenous nerve block administered via the adductor canal, using 0.25% Levobupivacaine as the local anesthetic. Postoperative pain was evaluated using the visual analogue scale (VAS). Additionally, Morphine consumption, adverse effects, and patient satisfaction were systematically assessed over the first 24 hours following the surgery.Results: The combination of popliteal nerve block and adductor canal block resulted in significant pain relief, with average VAS scores consistently remaining below 2 at all assessed time points. The mean dose of rescue Morphine administered during the first 24 hours post-surgery was 4.31 ± 2.287 mg. Additionally, all patients reported either satisfaction or high satisfaction with the pain relief provided by this combined anesthetic approach.Conclusion: The combined use of popliteal nerve block and adductor canal block proves to be an effective method for managing postoperative pain in below-knee surgeries. This approach significantly decreases the requirement for rescue Morphine and achieves high levels of patient satisfaction.
Keywords: Popliteal nerve block; below-knee surgery; postoperative pain management